(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article covers the historical development of Uzbek national clothing and its evolution in modern fashion. The formation of national clothing, its regional characteristics, its changes during the Soviet period and its revival after independence are discussed. The approaches of Uzbek designers to adapt national clothing to modern fashion and their successes in the international arena are also analyzed. The article also covers the role of national clothing in everyday life and the global fashion world.